HISTORY OF INNOVATION IN MUSIC, WITH REFERENCE TO DHRUPAD SINGING STYLE: संगीत में नवाचार का इतिहास, ध्रुपद गायन शैली के सन्दर्भ में - Taylor, Sharmila; Sisodia, Kamna (International Journal of Research -GRANTHAALAYAH, 2015)
Changing the tradition of history is a natural process of nature. In the context of the Dhrupad singing style in the Indian classical music world, if we take a historical view, the practice of singing Dhruva and Prabandha songs before this style was prevalent. The ritual form of Dhruva songs is found in Sanskrit drama texts from pre- to late India. Dhruva has an important place in terms of song composition. Even in the exorcisms used in the puvarang before the Natyarambha, the Dhruvas have special importance due to the use of musical instruments. Originally, the verses of songs which are used within the play are called Dhruva to make those situations intensified or to intensify the character of the characters in various situations of the play. They are also related to the lyricists due to their use of various parts of the lyricists. इतिहास की परम्परा में परिवर्तन होना प्रकृति की स्वाभाविक प्रक्रिया है। भारतीय शास्त्रीय संगीत जगत में ध्रुपद गायन शैली के सन्दर्भ मं हम ऐतिहासिक दृष्टि डालें तो इस शैली के पूर्व ध्रुवा एवं प्रबन्ध गीतों को गाने का प्रचलन था। ध्रुवा गीतों की परम्परा का क्रियात्मक रूप भरत के पूर्व से लेकर परवर्ती संस्कृत नाटक ग्रंथों में पाया जाता है। गीत रचना की दृष्टि से ध्रुवा का महत्त्वपूर्ण स्थान है। नाट्यारम्भ से पहले पूर्वरंग में प्रयुक्त बहिर्गीतों में भी ध्रुवाएं वाद्यप्रयोग की उपरंजक होने के कारण विशेष महत्व रखती हैं। मूलतः नाट्य की विभिन्न परिस्थितियों में रसानुभूति करा कर उन परिस्थितियों को तीव्र बनाने अथवा पात्रों के चरित्र को उभारने के लिए जिन छन्दोबद्ध गीतों का प्रयोग नाट्य के भीतर किया जाता है वे ध्रुवा कहलताी है। गीतकों के विभिन्न अंगों का इनमें प्रयोग होने के कारण ये गीतकों से भी सम्बन्ध है।